GAME TECHNOLOGIES OF LEARNING: EXPERIENCE OF USING THE "TANGRAM" - Losyeva Nataliyа; Puzyrov Volodymyr (Харк. нац. пед. ун-т імені Г. С. Сковороди. Харків., 2024)
The authors present the game learning technologies and depict the "Tangram" puzzle, which is a geometric constructor and a game at the same time. Some examples of its application in the training of pre-service teachers are presented.
Keywords: learning; game technologies; tangram; puzzle